2004
DOI: 10.1116/1.1722159
|View full text |Cite
|
Sign up to set email alerts
|

Efficient electron emissions from printed carbon nanotubes by surface treatments

Abstract: The fabrication of carbon nanotube (CNT) emitters with excellent field emission properties was described. CNT clusters synthesized by arc discharge were crushed, mixed with conductive pastes, and then screen-printed. In order to obtain efficient field emissions, the mechanical surface treatment was applied to the printed CNT films. The measurements of field emission carried out using a diode structure showed that the electron emission of the surface-treated CNT films uniformly turned-on with a field as low as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…The thin multi wall CNT that diameter is 6nm about used in this work (supplied by Iljin-nanotech, Korea). As a surface treatment, rubbing & peeloff method was adopted to protrude through efficient electron emissions from the emitter surface [7]. An additional firing process at a high temperature might be made to get rid of the residual organic species.…”
Section: Methodsmentioning
confidence: 99%
“…The thin multi wall CNT that diameter is 6nm about used in this work (supplied by Iljin-nanotech, Korea). As a surface treatment, rubbing & peeloff method was adopted to protrude through efficient electron emissions from the emitter surface [7]. An additional firing process at a high temperature might be made to get rid of the residual organic species.…”
Section: Methodsmentioning
confidence: 99%
“…Design of FED cathode surface features may require emitter lines to be bordered by electrically insulating dielectric surfaces. 7,8 During field emission, emitted electrons may acquire a wide range of initial trajectories because of the high geometric field enhancement around the CNT emitters. Adjacent dielectric surfaces are therefore bombarded by electrons with a shallow angle of incidence (see Fig.…”
Section: Field Emission Considerationsmentioning
confidence: 99%
“…7 Field emission devices based on CNTs have been realized using a variety of methods ranging from the chemical vapor deposition (CVD) process, assembling in more complex systems and using screen printed techniques. [16][17][18][19][20][21][22][23][24][25] Several studies have demonstrated an enhancement of electron field emission after laser treatments performed both on screen-printed CNTs and those created using CVD techniques. To achieve high current densities and stability, postsynthesis treatment can be adopted, including thermal, chemical, and laser treatments.…”
Section: Introductionmentioning
confidence: 99%